Barriers to accessing follow up care in post-hospitalized trauma patients in Moshi, Tanzania: A mixed methods study. - Anjni Patel Joiner; Anna Tupetz; Timothy Antipas Peter; Julius Raymond; Victoria Gerald Macha; João Ricardo Nickenig Vissoci; Catherine Staton (Public Library of Science (PLoS), 2022)
Disproportionately high injury rates in Sub-Saharan Africa combined with limited access to care in both the acute injury phase and for injury patients requiring continued care after hospital discharge remains a challenge. We aimed to characterize barriers to transportation and access to care in a cohort of post-hospitalized injury patients in Moshi, Tanzania. This was a mixed-methods study of a prospective cohort of trauma registry patients presenting to Kilimanjaro Christian Medical Center between August 2018 and January 2020. We conducted standardized patient/family surveys and in-depth interviews at a 2-week follow up visit after hospital discharge, and focus groups with healthcare providers. Quantitative results were analyzed using descriptive statistics and multivariable logistic regression using R statistical software. Qualitative results were analyzed using thematic analysis through an iterative process using NVivo software. A total of 1,365 patients were enrolled in the trauma registry, with 169 patients followed up at 2 weeks. Over half of patients at follow-up, 101 (59.8%), reported challenges in traveling. The majority of patients were male (80.3%). Difficulty in traveling since injury was associated with female gender (aOR 5.85 [95% CI 1.20-33.59]) and a need for non-family members escorts for travel (aOR 7.10 [95% CI 1.43-41.66]). Those who reported assault or fall as the mechanism of injury as compared to road traffic injury and had health insurance were less likely to report challenges in traveling (aOR 0.19 [95% CI 0.03-0.90]), 0.11 [95% CI 0.01-0.61], 0.14 [95% 0.02-0.80]). Transportation barriers that emerged from qualitative data included inability to use regular means of transportation, financial challenges, physical barriers, rigid compliance to physician orders, access to healthcare, and social support barriers. Our findings demonstrate several areas to address transportation barriers for post-injury patients in Tanzania. Educational interventions such as clarification of doctors' orders of strict bedrest, provision of vouchers to support financial challenges and alternate means of transportation given physical barriers and reliance on social support may address some of these barriers.